The Effects of Reactive Oxygen and Nitrogen Species (RONS) Produced by Surface Dielectric Barrier Discharge (SDBD) Non-Thermal Plasma with Treatment Time and Distance Variations to Kill Escherichia coli - Renaldo Apriandi Kasa; Unggul Pundjung Juswono; Dionysius J. D. H. Santjojo (Science and Technology Indonesia, 2023)
Research on the inactivation of Escherichia coli causing diarrheal disease using non-thermal plasma SDBD has been carried out. SDBD is a new technique for non-thermal plasma generation with several advantages: low power generation, comprehensive treatment area coverage, and reducing the potential effects of burning and drying tissue. This study aimed to analyze the effect of treatment time variations, namely 0 as control, 60, 75, 90, 105, and 120 seconds and treatment distance variations of 3, 6, 9, 12, and 15 mm of non-thermal plasma treatment of SDBD on E. coli. The results of the non-thermal plasma SDBD treatment with variations in time and distance showed that the longer the treatment time, the more bacterial cells died. Colony counts decreased to 4.33 x 107 CFU/mL compared to the control, 409 x 107 CFU/mL, with a treatment time variation of 120 seconds, yielding the best treatment results. At the same time, the results of the treatment for variations in the non-thermal plasma distance of SDBD showed that the smaller the treatment distance, the greater the bacterial death rate, with the best treatment results at a 3 mm treatment interval, with colony counts of 8 x 107 CFU/mL, compared to 409 x 107 CFU/mL in control. Based on these results, SDBD non-thermal plasma treatment can be used to inactivate or kill bacteria with effectiveness in killing bacteria depending on the length of treatment time and the distance of treatment.